2019
DOI: 10.1109/jstars.2019.2906053
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Computational Geometry Method for Obtaining Accurate Remotely Sensed Products via Convex Hulls With Dynamic Weights: A Case Study With Leaf Area Index

Abstract: Most retrieval functions used in remote sensing assume that the land surface is homogeneous. When those functions are used at coarse spatial resolution for heterogeneous surfaces, scale effects might appear. This paper tries to develop an improved computational geometry method (ICGM) upscaling model that takes into consideration the actual distribution of surface measurements by using dynamic weights for the upper and lower envelopes of a convex hull. By aggregating to a series of simulated data at coarse spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Performing analysis involving the Earth's surface is a wellknown issue in Geography and Satellite Applications [33], [34]. Involving astrodynamics such as Constellation-to-ground coverage analysis and non-spherical models of the Earth further increases the complexity of the problem [35], [36]. Since dealing with any non-euclidean plane is challenging, the issue is usually approached by making compromises, simplifications, and assumptions.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Performing analysis involving the Earth's surface is a wellknown issue in Geography and Satellite Applications [33], [34]. Involving astrodynamics such as Constellation-to-ground coverage analysis and non-spherical models of the Earth further increases the complexity of the problem [35], [36]. Since dealing with any non-euclidean plane is challenging, the issue is usually approached by making compromises, simplifications, and assumptions.…”
Section: Modelmentioning
confidence: 99%
“…We identify three main items in the case of the study of the Earth's surface: i) assuming a spherical Earth model, ii) restricting analysis on small regions, and iii) restricting analysis far from the poles. Some provide the bases for comprehensible and easy-to-implement methods, which are precise enough for specific applications [36], [37], but fall short when pushed outside their limits.…”
Section: Modelmentioning
confidence: 99%
“…On the heterogeneous surfaces, the skewness and kurtosis of the random variable may be large, and the AM-GM algorithm may exhibit a better performance for the computation of µ and LAI scaling bias. In the improved CGM, the relative errors decreased from 3.35%, 11.01%, and 19.62% to an average of 0.28%, 1.48%, and 5.16%, respectively, at kilometer scales [26]. Jiang et al indicated that the LAI scaling bias decreased to around 0.27 by the TSEM, Wavelet-Fractal (WF), and Fractal theory (TT) [30].…”
Section: Algorithm Comparisonmentioning
confidence: 99%
“…However, empirical methods require external factors that limit their applicability. On the other hand, a series of universal methods have been provided [8,[21][22][23][24][25][26]. For instance, the computational geometry method (CGM) sets the upper and lower envelopes of the retrieval model to achieve accurate parameter estimation at coarse resolutions [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation